Respostas

A melhor resposta!
2014-05-16T17:24:24-03:00
x+y+k=6  (I)
2x-y+k=12  (II)
x+2y+5k=17
  (III)

(I) e  (II)
x+y+k=6 (-2
2x-y+k=12
_________
-2x - 2y - 2k = -12
 2x - y  +    k= 12
_______________
       -3y - k = 0

(I) e (III)
x + y + k = 6 (-1
x+ 2y + 5k = 17
______________
- x - y - k = -6
  x + 2y + 5k = 17
_______________
      y + 4k = 11

Resultado da (I) com a (II) e (I) com a (III)
Valor de K
  -3y - k = 0
   y + 4k = 11 (3
____________
  -3y  -     k = 0
   3y + 12k = 33
_______________
       11k = 33
           k = 33/11
           k = 3

Valor de Y
-3y - k = 0
-3y - 3 = 0
-3y = 3 (-1
 3y = - 3
  y = - 3/3
  y = - 1

Valor de X
x + y + k = 6
x + (-1 + 3 = 6
x - 1 + 3 = 6
x + 2 = 6
x = 6 - 2
x = 4

Para conferir se esta correto;
x + y + k = 6
4 + (-1 + 3 = 6
4 - 1 + 3 = 6
3 + 3 = 6
6 = 6
s{(4,-1,3);}SPD
2 5 2